Nutritional Status and Blood Profile amongst Patient withChildand Maternal Leprosy in Endemic and Non-Endemic Area of Indonesia - Flora Ramona Sigit Prakoeswa; Yohanes Aditya Adhi Satria; Budi Prasetyo; Santi Martini; Muhammad Yulianto Listiawan; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Leprosy remains endemic in several country, where the disease is still considered as a health burden. The development of the disease is determined by several factors, amongst which that play significant role are close household contact and impaired immunity. Maternal index case significantly associated with leprosy case in children and nutritional status plays a pivotal role in shaping the immune response against the bacteria Mycobacterium leprae. Thus, this paper aims to evaluatethe association between nutritional status and leprosy, especially in maternal and child leprosy. The study was conducted in Tuban, Indonesia. We foundsignificant difference in haemoglobin, red blood cells, and haematocrit levels in subject with maternal leprosy in the group of child without leprosy and leprous mother compared to the control group. The difference in haemoglobin and haematocrit level are also associated with child leprosy in the group of child with leprosy and mother with leprosy.In addition, although no significant association on BMI were observed, we found that the child whose mother contracted leprosy has a lower BMI compared to the other groups